Mackie on Practical Reason - Phillips, David (Ethical theory and moral practice, 2007)
I argue that John Mackie’s treatment of practical reason is both attractive and unjustly neglected. In particular, I argue that it is importantly different from, and much more plausible than, the kind of instrumentalist approach famously articulated by Bernard Williams. This matters for the interpretation of the arguments for Mackie’s most famous thesis: moral scepticism, the claim that there are no objective values. Richard Joyce has recently defended a version or variant of moral scepticism by invoking an instrumentalist theory like Williams’. I argue that this is a serious strategic mistake.